Feeding Strategy for The Development of Buffalo Farming - Suhubdy . (Indonesian Center for Animal Research and Development, 2007)
Until recently, cattle meat is believed as a dominant source of red meat that fulfills the market demands of Indonesia’s consumers. Meat demands tend to increase in the future caused by the increase income of human beings. As a consequence, the population of cattle tends to decrease and their role as meat producer should be in part or fully overcome and substituted by other ruminant livestock. Buffalo is one of the native ruminant livestock breeds of Indonesia that nutritionally and physiologically is not so different from cattle. This animal may be suitable and affordable to enhance the meat production. However, the present progress of buffalo population is not as good as cattle. This may be to some extent, related to the governmental policy that never lists it for a long time, as a high priority program in livestock development. Beside this constraint, buffalo has some strength to be optimized by improving its genetic potentiality and environmental related aspects. This paper deals with the effort of improving the nutrition and feed availability of buffalo with special focus on the applied feed technology. In the future, this approach will hopefully accelerate the buffalo population rate. Key words: Buffalo, feed technology, forage, red meat, milk, nutrition, livestock farming